Max Liniger-Goumaz, Historical Dictionary of Equatorial Guinea (African Historical Dictionary, No. 21), The Scarecrow Press Inc., Metuchen y Londres, 1988. - Wa Githiora, Cege (Estudios de Asia y África, 1990)
-